Adrenal insufficiency from steroid-containing complementary therapy: importance of detailed history. (26th July 2019) - Kempegowda, Punith; Quinn, Lauren; Shepherd, Lisa; Kauser, Samina; Johnson, Briony; Lawson, Alex; Bates, Andrew
Summary: A 62-year-old Asian British female presented with increasing tiredness. She had multiple co-morbidities and was prescribed steroid inhalers for asthma. She had also received short courses of oral prednisolone for acute asthma exacerbations in the last 2 years. Unfortunately, the frequency and dose of steroids for asthma was unclear from history. Her type 2 diabetes mellitus (DM) control had deteriorated over a short period of time (HbA1c: 48–85 mmol/mol). Blood tests revealed undetectable cortisol and ACTH (<28 mmol/L, <5.0 ng/L). Renin, electrolytes and thyroid function were within normal limits. A diagnosis of secondary adrenal insufficiency, likely due to long-term steroid inhaler and recurrent short courses of oral steroids for asthma exacerbations was made. Patient was commenced on hydrocortisone 10 mg, 5 mg and 5 mg regimen. Steroid inhaler was discontinued following consultation with respiratory physicians. Despite discontinuation of inhaled steroids, patient continued not to mount a response to Synacthen®. Upon further detailed history, patient admitted taking a 'herbal' preparation for chronic osteoarthritic knee pain. Toxicology analysis showed presence of dexamethasone, ciprofloxacin, paracetamol, diclofenac, ibuprofen and cimetidine in the herbal medication. Patient was advised to discontinue her herbal preparation. We believe the cause of secondary adrenal insufficiency in our patient was the herbal remedy containing dexamethasone, explaining persistent adrenal suppression despite discontinuation of all prescribed steroids, further possibly contributing to obesity, hypertension and suboptimal control of DM. In conclusion, a comprehensive drug history including herbal and over-the-counter preparations should be elucidated. Investigation for the presence of steroids in these preparations should be considered when patients persist to have secondary adrenal insufficiency despite discontinuation of prescribed steroid medications. Learning points: The likelihood of complementary and alternative medicines (CAMs) in medication-induced secondary adrenal insufficiency should be considered in any patient presenting with potential symptoms of adrenal insufficiency. If the contents of CAM preparation cannot be ascertained, toxicology screening should be considered. Patients should be advised to stop taking CAM preparation when it contains steroids and hydrocortisone replacement therapy commenced, with periodic reassessment of adrenal function, and then if indicated weaned accordingly. Patients should be informed about the contents of CAM therapies, so they can make a truly informed choice regarding the risks and benefits. This case also highlights a need to increase regulatory processes over CAM therapies, given their propensity to contain a number of undisclosed medications and potent steroids.